3D porous graphene synthesised using different hydrothermal treatment times for the removal of lead ions from an aqueous solution. (1st May 2017) - Zhou, Fang; Yu, Jingang; Jiang, Xinyu
Abstract : Three‐dimensional porous graphene (3D PG) synthesised using different hydrothermal treatment times was obtained by an environmentally friendly freeze‐drying method. The as‐prepared 3D PG was characterised by Raman spectroscopy, scanning electron microscopy, thermogravimetric analysis and Brunauer–Emmett–Teller measurement. The results showed that 3D porous graphene synthesised over a shorter hydrothermal treatment time had more graphitic structural defects and oxygen‐containing functional groups. Adsorption experiments were conducted to investigate the influence of hydrothermal treatment time on the removal of lead ions. In addition, it was revealed that shorter hydrothermal treatment times led to higher adsorption capacities for the 3D PG. This study provides the first evidence of the hydrothermal treatment time of 3D PG playing a critical role in the removal of metal ions from an aqueous solution.